Protective Effect of Vitamin-D Supplementation in Patients of Acute Coronary Syndrome During COVID-19 Pandemic - Sidra Jabeen, Humaira Fayyaz Khan, Samia Sarwar, Mehvish Ashfaq, Ayesha Zafar, Ummara Aslam, Shmyla Hamid (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Objectives: To determine the effect of vitamin-D supplementation in patients of the acute coronary syndrome and its role if any in preventing COVID-19 infection. Study design: Prospective clinical trial Place and duration: Armed Forces Institute of Cardiology in collaboration with Riphah International University Material and methods: The study was conducted by recruiting 40 patients, diagnosed with the acute coronary syndrome. After the PCI procedure during their hospital stay, 20 of them were given a single shot of vitamin-D supplement in a dose of 200000 IU while the rest of 20 were allocated as controls. Patients were instructed to follow the SOPs strictly and were followed up for incidence of coronavirus disease after 2 months. Detailed history regarding their stay during lockdown was taken. Independent sample t-test was used to compare the two groups with p≤0.05 considered as significant. Results: The patients enrolled in the study were assessed for pre and post-intervention levels for vitamin-D. After the intervention the levels in the experimental group were increased to 30.74±18.40 ng/ml (p=0.000***) from a mean value of 18.27 ±8.98 ng/ml. Among the control group, eight out of 40 patients tested positive for COVID-19 while none among the experimental group got the disease (p=0.016*). The results of the follow-up interview showed that the patients followed the precautions for COVID protection during the pandemic. Conclusion: Vitamin-D supplementation during lockdown may prove beneficial in protection against COVID-19.